Laser direct writing high-speed high-precision copper-based photoresist and semiconductor patterning method thereof
Patent Information
- Application Number
- CN202310701857.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-06-14
AI Technical Summary
[0005]为了满足高精度器件和模板的制造需要,亚100nm甚至亚50nm的高精度激光直写光刻胶是必须的,且为了缩短制造时间,降低制造成本,这些光刻胶也必须具备高速高灵敏的特点,而高精度和高速在激光直写光刻胶中通常难以同时具备
[0023]作为优选,步骤S4中,热解时的气氛为空气气氛,热解温度为500-1000℃,升温速率为1-10℃/min,降温速率为自然降温。
Smart Images

Figure CN116719208B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of micro-nano structure manufacturing, and particularly relates to a high-speed, high-precision laser direct-write copper-based photoresist and its semiconductor patterning method. Background Technology
[0002] Laser direct writing is a maskless photolithography technique. It involves focusing a laser beam into a small spot, then moving the spot using a galvanometer, rotating mirror, or stage to expose the photoresist. After development, the desired micro / nano pattern is left. Traditional ultraviolet lithography requires a photomask with the designed pattern. Ultraviolet light passes through the transparent portion of the photomask and is projected onto the photoresist film, exposing it. The advantage of laser direct writing is that it can write arbitrary patterns without a photomask. The laser spot's movement path is controlled by programming to expose the photoresist at specific locations.
[0003] In terms of writing speed, laser direct writing has a significant disadvantage compared to ultraviolet lithography. Taking a 6-inch substrate as an example, the typical exposure time for ultraviolet lithography is less than 1 minute, while the time for laser direct writing to cover a 6-inch substrate is tens or even hundreds of hours. This is one of the reasons why laser direct writing is currently difficult to use for mass production. However, due to its maskless manufacturing method, it is very suitable for manufacturing template-type products such as photomasks and nanoimprint stencils.
[0004] The highest precision of currently used laser direct writing photoresists is around 100nm, while commercially available laser direct writing photoresists generally have a precision of over 150nm.
[0005] To meet the manufacturing needs of high-precision devices and templates, high-precision laser-direct-write photoresists with sub-100nm or even sub-50nm resolution are essential. Furthermore, to shorten manufacturing time and reduce costs, these photoresists must also possess high speed and high sensitivity. However, high precision and high speed are typically difficult to achieve simultaneously in laser-direct-write photoresists. In addition, most commercially available laser-direct-write photoresists are all-organic systems, lacking functional laser-direct-write photoresists that combine organic and inorganic components. Functional laser-direct-write photoresists capable of patterning functional materials are also urgently needed. Summary of the Invention
[0006] The purpose of this invention is to address the limitations of existing technologies by providing a high-speed, high-precision laser-written copper-based photoresist and its semiconductor patterning method.
[0007] The objective of this invention is achieved through the following technical solution:
[0008] In a first aspect, the present invention provides a laser-written copper-based photoresist, comprising a copper-based photoresist monomer, a two-photon initiator, an inhibitor, and a solvent; wherein the inhibitor is at least one selected from 2,2,6,6-tetramethylpiperidine-nitro-oxide (TEMPO), bis(2,2,6,6-tetramethyl-4-piperidinyl-1-oxy) sebacate (BTPOS), and 5,5-dimethyl-1-pyrrolidone-N-oxide (DMPO), which inhibits linewidth growth by capturing free radicals diffused during polymerization; wherein in the laser-written copper-based photoresist, the mass of the copper-based photoresist monomer is 2-8% of the mass of the solvent, the mass of the two-photon initiator is 0.25%-2.5% of the mass of the copper-based photoresist monomer, and the mass of the inhibitor is 0.25%-2.5% of the mass of the copper-based photoresist monomer.
[0009] Preferably, the solvent is propylene glycol methyl ether acetate (PGMEA), propylene glycol methyl ether (PGME), or a mixture of both.
[0010] Preferably, the two-photon initiator is 7-diethylamino-3-thiophenecarboxycoumarin (DETC).
[0011] Preferably, the copper-based photoresist monomer is hydrated copper methacrylate, copper acrylate, or a mixture of both.
[0012] Preferably, the laser direct-write copper-based photoresist is composed of copper-based photoresist monomers, two-photon initiators, inhibitors, and solvents.
[0013] The laser direct-write copper-based photoresist described in this invention can be obtained through conventional steps, namely, dissolving copper-based photoresist monomers, two-photon initiators and inhibitors in a solvent in a certain proportion, fully dissolving by ultrasonication, filtering with a 0.22μm filter membrane, fully mixing on a mixer, and then storing under cold (e.g., at 4°C).
[0014] Secondly, the present invention provides a semiconductor patterning method based on the laser-written copper-based photoresist, comprising the following steps:
[0015] S1: Obtain laser-written copper-based photoresist;
[0016] S2: Using a spin coater, laser-written copper-based photoresist is spin-coated onto the substrate to form a transparent copper-based photoresist film;
[0017] S3: A femtosecond laser direct writing device is used, which uses a femtosecond laser as a light source. The copper-based photoresist film is induced to polymerize at the designed position by galvanometer writing. The design pattern is obtained by developing the film with primary and secondary developer solutions.
[0018] S4: The pattern etched by the obtained copper-based photoresist is pyrolyzed in an air atmosphere using a heating device. During the pyrolysis process, the organic components in the pattern are oxidized and leave the system, while the copper element is oxidized to copper oxide, resulting in a micro-nano pattern of P-type semiconductor copper oxide.
[0019] Preferably, in step S2, the spin coating speed used is 1500-5000 rpm and the spin coating time is 60 s.
[0020] Preferably, in step S3, the wavelength of the femtosecond laser is between 525 and 780 nm.
[0021] Preferably, in step S3, the energy range used for writing the copper-based photoresist is 3-50mW, and the speed range is 1000μm / s-200000μm / s (200mm / s).
[0022] Preferably, in step S3, the primary developer used for development is at least one of propylene glycol methyl ether acetate, propylene glycol monomethyl ether, and propylene glycol monoethyl ether, and the secondary developer is isopropanol.
[0023] Preferably, in step S4, the atmosphere during pyrolysis is air, the pyrolysis temperature is 500-1000℃, the heating rate is 1-10℃ / min, and the cooling rate is natural cooling.
[0024] As a further preferred option, if the pyrolysis temperature of step S4 is 500-600℃, then the substrate used is glass; if the pyrolysis temperature of step S4 is higher than 600℃ but ≤1000℃, then the substrate used is quartz.
[0025] Compared with existing technologies, the advantages of this invention are as follows: It provides a high-speed, high-precision copper-based photoresist for laser direct writing and its semiconductor patterning method. The copper-based photoresist is polymerized under a 780nm femtosecond laser, achieving a precision below 91nm, with a maximum precision reaching sub-50nm, which is 1 / 15 of the wavelength, and exhibiting excellent line morphology. While maintaining high precision, the maximum writing speed can reach 200mm / s, meeting the requirements of high-speed, high-precision laser direct writing. Furthermore, the solid form of the photoresist is suitable for large-area writing and applicable to the fabrication of large-area two-dimensional patterns. After the pattern written on the copper-based photoresist is pyrolyzed in an air atmosphere, corresponding copper oxide micro / nano patterns are obtained. Copper oxide is a P-type semiconductor and can be used to manufacture semiconductor micro / nano devices. Using this high-speed, high-precision copper-based laser direct writing photoresist and its semiconductor patterning method, high-speed, high-precision laser direct writing direct fabrication of copper oxide semiconductor micro / nano devices can be achieved. Attached Figure Description
[0026] Figure 1 Copper oxide lines etched for copper-based photoresist A;
[0027] Figure 2 The XRD pattern of copper-based photoresist A after UV curing and annealing;
[0028] Figure 3 Copper oxide lines etched by copper-based photoresist B;
[0029] Figure 4 Copper oxide lines etched by copper-based photoresist C;
[0030] Figure 5 Copper oxide lines etched by copper-based photoresist D;
[0031] Figure 6 Copper oxide lines etched by copper-based photoresist E;
[0032] Figure 7 Copper oxide lines etched by copper-based photoresist F;
[0033] Figure 8 Copper oxide lines etched by copper-based photoresist G;
[0034] Figure 9 Copper oxide lines etched by copper-based photoresist H;
[0035] Figure 10 Copper oxide lines etched by copper-based photoresist I;
[0036] Figure 11 Copper oxide lines etched by copper-based photoresist J;
[0037] Figure 12 To compare the copper oxide lines etched by copper-based photoresist A;
[0038] Figure 13 To compare the zinc oxide lines etched by zinc-based photoresist A;
[0039] Figure 14 This is a schematic diagram of the femtosecond laser direct writing device used in an embodiment of the present invention. Detailed Implementation
[0040] The present invention will be further described below with reference to preferred embodiments and accompanying drawings. The specific details described in the following embodiments are illustrative rather than restrictive, and will help those skilled in the art to further understand the present invention, but should not be construed as limiting the present invention in any way. It should be noted that those skilled in the art can make some adjustments and improvements without departing from the basic concept and method of the present invention. These all fall within the protection scope of the present invention.
[0041] The femtosecond laser direct writing device used in the embodiments of the present invention is as follows: Figure 1As shown. Unless otherwise specified in the examples, conditions should be followed according to standard conditions or the manufacturer's recommendations. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0042] Example 1
[0043] 0.5g of copper acrylate was dissolved in 10g of propylene glycol methyl ether acetate, 1.25mg of two-photon initiator DETC and 1.25mg of TEMPO were added, followed by sonication for 20 minutes to promote dissolution. The mixture was then filtered twice through a 0.22μm filter membrane to obtain copper-based photoresist A. After mixing on a mixer for 24h, the mixture was stored at 4℃.
[0044] Copper-based photoresist A was dropped onto a glass substrate and spin-coated at 3000 rpm for 60 seconds to obtain a thin film of copper-based photoresist A.
[0045] The etching process uses a 780nm femtosecond laser. The laser focus is changed by a galvanometer system to induce the polymerization of monomers at selected locations in the copper-based photoresist film. The energy used for etching is 50mW, and the speed is 200000μm / s.
[0046] After the inscription is completed, it is developed in propylene glycol methyl ether acetate for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0047] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 500℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0048] Micro- and nano-patterns of copper oxide can be obtained after pyrolysis and characterized using SEM, such as... Figure 1 The line width of the inscribed lines is approximately 47 nm.
[0049] Due to their small size, micro- and nano-structures are difficult to directly perform XRD testing. To characterize the composition of the pyrolyzed sample, 0.5 g of copper-based photoresist A was cured under 365 nm UV light and then pyrolyzed under the same conditions. The pyrolyzed sample was then characterized by XRD. Figure 2 The XRD pattern of the pyrolyzed sample showed that the diffraction peaks matched the copper oxide standard card, indicating that the sample was composed of copper oxide.
[0050] Example 2
[0051] 0.2g of copper acrylate was dissolved in 10g of propylene glycol monomethyl ether, 4mg of two-photon initiator DETC and 4mg of BTPOS were added, and then sonicated for 20 minutes to promote dissolution. The mixture was filtered twice through a 0.22μm filter membrane to obtain copper-based photoresist B. After mixing on a mixer for 24h, it was stored at 4℃.
[0052] Copper-based photoresist B was dropped onto a glass substrate and spin-coated at 1500 rpm for 60 seconds to obtain a thin film of copper-based photoresist B.
[0053] The etching process uses a 780nm femtosecond laser. The laser focus is changed by a galvanometer system to induce polymerization of monomers at selected locations in the copper-based photoresist film. The energy used for etching is 10mW, and the speed is 5000μm / s.
[0054] After the inscription is completed, it is developed in propylene glycol monomethyl ether for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0055] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 500℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0056] Micro- and nano-patterns of copper oxide were obtained after pyrolysis and characterized using SEM. The linewidth was 65 nm. Figure 3 .
[0057] Example 3
[0058] 0.5g of copper acrylate was dissolved in 10g of propylene glycol monomethyl ether, and 2.5mg of two-photon initiator DETC, 1.25mg of BTPOS and 1.25mg of TEMPO were added. The mixture was then sonicated for 20 minutes to promote dissolution. The solution was filtered twice through a 0.22μm filter membrane to obtain copper-based photoresist C. The solution was mixed on a homogenizer for 24 hours and then stored at 4°C.
[0059] Copper-based photoresist C was dropped onto a glass substrate and spin-coated at 2000 rpm for 60 seconds to obtain a thin film of copper-based photoresist C.
[0060] The etching process uses a 780nm femtosecond laser. The laser focus is changed by a galvanometer system to induce polymerization of monomers at selected locations in the copper-based photoresist film. The energy used for etching is 15mW, and the speed is 8000μm / s.
[0061] After the inscription is completed, it is developed in propylene glycol monomethyl ether for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0062] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 500℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0063] Micro- and nano-patterns of copper oxide were obtained after pyrolysis and characterized using SEM. The linewidth was 57 nm. Figure 4 .
[0064] Example 4
[0065] 0.8g of copper acrylate was dissolved in 10g of propylene glycol monomethyl ether, 8mg of two-photon initiator DETC and 8mg of DMPO were added, and then sonicated for 20 minutes to promote dissolution. The mixture was filtered twice through a 0.22μm filter membrane to obtain copper-based photoresist D. After mixing on a mixer for 24h, it was stored at 4℃.
[0066] Copper-based photoresist D was dropped onto a quartz substrate and spin-coated at 4000 rpm for 60 seconds to obtain a thin film of copper-based photoresist D.
[0067] The etching process uses a 780nm femtosecond laser. The laser focus is changed by a galvanometer system to induce polymerization of monomers at selected locations in the copper-based photoresist film. The energy used for etching is 3mW, and the speed is 1000μm / s.
[0068] After the inscription is completed, it is developed in propylene glycol monomethyl ether for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0069] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 700℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0070] Micro- and nano-patterns of copper oxide were obtained after pyrolysis and characterized using SEM. The linewidth was 67 nm. Figure 5 .
[0071] Example 5
[0072] 0.5g of copper acrylate was dissolved in 10g of propylene glycol monoethyl ether, 5mg of two-photon initiator DETC and 5mg of DMPO were added, and then sonicated for 20 minutes to promote dissolution. The mixture was filtered twice through a 0.22μm filter membrane to obtain copper-based photoresist E. After mixing on a mixer for 24h, it was stored at 4℃.
[0073] Copper-based photoresist E was dropped onto a glass substrate and spin-coated at 2000 rpm for 60 seconds to obtain a thin film of copper-based photoresist E.
[0074] The etching process uses a 780nm femtosecond laser. The laser focus is changed by a galvanometer system to induce polymerization of monomers at selected locations in the copper-based photoresist film. The energy used for etching is 25mW, and the speed is 50000μm / s.
[0075] After the inscription is completed, it is developed in propylene glycol monoethyl ether for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0076] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 600℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0077] Micro- and nano-patterns of copper oxide were obtained after pyrolysis and characterized using SEM. The linewidth was 53 nm. Figure 6 .
[0078] Example 6
[0079] 0.5 g of hydrated copper methacrylate was dissolved in a mixture of 10 g of propylene glycol monomethyl ether and propylene glycol monoethyl ether (the mass ratio of the two solvents was 1:1). 5 mg of two-photon initiator DETC, 2.5 mg of DMPO and 2.5 mg of BTPOS were added, followed by sonication for 20 minutes to promote dissolution. The mixture was then filtered twice through a 0.22 μm filter membrane to obtain copper-based photoresist F. After homogenization for 24 h, the mixture was stored at 4 °C.
[0080] Copper-based photoresist F was dropped onto a quartz substrate and spin-coated at 2000 rpm for 60 seconds to obtain a thin film of copper-based photoresist F.
[0081] The etching process uses a 780nm femtosecond laser. The laser focus is changed by a galvanometer system to induce polymerization of monomers at selected locations in the copper-based photoresist film. The energy used for etching is 20mW, and the speed is 10000μm / s.
[0082] After the inscription is completed, it is developed in propylene glycol monomethyl ether for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0083] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 800℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0084] Micro- and nano-patterns of copper oxide were obtained after pyrolysis and characterized using SEM. The linewidth was 82 nm. Figure 7 .
[0085] Example 7
[0086] 0.25 g of copper acrylate and 0.25 g of hydrated copper methacrylate were dissolved in a mixture of 10 g of propylene glycol methyl ether acetate and propylene glycol monoethyl ether (the mass ratio of the two solvents was 1:1). 5 mg of two-photon initiator DETC, 2.5 mg of TEMPO and 2.5 mg of DMPO were added, followed by sonication for 20 minutes to promote dissolution. The mixture was then filtered twice through a 0.22 μm filter membrane to obtain copper-based photoresist G. After mixing for 24 h in a homogenizer, the mixture was stored at 4 °C.
[0087] Copper-based photoresist G was dropped onto a quartz substrate and spin-coated at 2000 rpm for 60 seconds to obtain a thin film of copper-based photoresist G.
[0088] The etching process uses a 780nm femtosecond laser. The laser focus is changed by a galvanometer system to induce polymerization of monomers at selected locations in the copper-based photoresist film. The energy used for etching is 35mW, and the speed is 100000μm / s.
[0089] After the inscription is completed, it is developed in propylene glycol monomethyl ether for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0090] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 800℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0091] Micro- and nano-patterns of copper oxide were obtained after pyrolysis and characterized using SEM. The linewidth was 77 nm. Figure 8 .
[0092] Example 8
[0093] 0.6 g of hydrated copper methacrylate was dissolved in 10 g of propylene glycol methyl ether acetate, 3 mg of two-photon initiator DETC and 3 mg of TEMPO were added, and then sonicated for 20 minutes to promote dissolution. The mixture was filtered twice through a 0.22 μm filter membrane to obtain copper-based photoresist H. After mixing on a mixer for 24 h, it was stored at 4 °C.
[0094] Copper-based photoresist H was dropped onto a glass substrate and spin-coated at 5000 rpm for 60 seconds to obtain a thin film of copper-based photoresist H.
[0095] The etching process uses a 780nm femtosecond laser. The laser focus is changed by a galvanometer system to induce polymerization of monomers at selected locations in the copper-based photoresist film. The energy used for etching is 15mW, and the speed is 30000μm / s.
[0096] After the inscription is completed, it is developed in propylene glycol methyl ether acetate for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0097] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 600℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0098] Micro- and nano-patterns of copper oxide were obtained after pyrolysis and characterized using SEM. The linewidth was 86 nm. Figure 9 .
[0099] Example 9
[0100] 0.5 g of hydrated copper methacrylate was dissolved in a mixture of 10 g of propylene glycol methyl ether acetate and propylene glycol monomethyl ether (the mass ratio of the two solvents was 1:1). 10 mg of two-photon initiator DETC and 10 mg of TEMPO were added, followed by sonication for 20 minutes to promote dissolution. The mixture was then filtered twice through a 0.22 μm filter membrane to obtain copper-based photoresist I. After mixing on a homogenizer for 24 h, it was stored at 4 °C.
[0101] Copper-based photoresist I was dropped onto a quartz substrate and spin-coated at 5000 rpm for 60 seconds to obtain a thin film of copper-based photoresist I.
[0102] The etching process uses a 780nm femtosecond laser. The laser focus is changed by a galvanometer system to induce polymerization of monomers at selected locations in the copper-based photoresist film. The energy used for etching is 35mW, and the speed is 100000μm / s.
[0103] After the inscription is completed, it is developed in propylene glycol methyl ether acetate for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0104] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 1000℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0105] Micro- and nano-patterns of copper oxide were obtained after pyrolysis and characterized using SEM. The linewidth was 91 nm. Figure 10 .
[0106] Example 10
[0107] 0.5g of hydrated copper methacrylate was dissolved in 10g of propylene glycol methyl ether acetate, 10mg of two-photon initiator DETC and 10mg of TEMPO were added, and then sonicated for 20 minutes to promote dissolution. The mixture was filtered twice through a 0.22μm filter membrane to obtain copper-based photoresist J. After mixing on a mixer for 24h, it was stored at 4℃.
[0108] Copper-based photoresist J was dropped onto a quartz substrate and spin-coated at 5000 rpm for 60 seconds to obtain a thin film of copper-based photoresist J.
[0109] The etching process uses a 780nm femtosecond laser. The laser focus is changed by a galvanometer system to induce polymerization of monomers at selected locations in the copper-based photoresist film. The energy used for etching is 40mW, and the speed is 120000μm / s.
[0110] After the inscription is completed, it is developed in propylene glycol methyl ether acetate for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0111] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 1000℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0112] Micro- and nano-patterns of copper oxide were obtained after pyrolysis and characterized using SEM. The linewidth was 76 nm. Figure 11 .
[0113] As can be seen from the images of the copper oxide patterns etched in Examples 1 to 10, the lines etched by this method are clear, with good line shape and uniformity, and a minimum resolution of sub-50 nm. This method can obtain arbitrary copper oxide micro- and nano-patterns through laser direct writing, providing a new approach for the fabrication of copper oxide semiconductor devices.
[0114] Comparative Example 1
[0115] 0.5g of copper acrylate was dissolved in 10g of propylene glycol methyl ether acetate, and 1.25mg of two-photon initiator DETC was added. The mixture was then sonicated for 20 minutes to promote dissolution. The mixture was filtered twice through a 0.22μm filter membrane to obtain the control copper-based photoresist A. The mixture was homogenized on a mixer for 24h and then stored at 4°C.
[0116] The contrast copper-based photoresist A was dropped onto a glass substrate and spin-coated at 3000 rpm for 60 seconds to obtain a thin film of contrast copper-based photoresist A.
[0117] The etching process uses a 780nm femtosecond laser. The laser focus is changed by a galvanometer system to induce the polymerization of monomers at selected locations in the copper-based photoresist film. The energy used for etching is 50mW, and the speed is 200000μm / s.
[0118] After the inscription is completed, it is developed in propylene glycol methyl ether acetate for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0119] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 500℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0120] Micro- and nano-patterns of copper oxide can be obtained after pyrolysis and characterized using SEM, such as... Figure 12 The line width of the inscribed lines was approximately 120 nm. This comparative example did not add any inhibitor, and all other conditions were the same as in Example 1. The line width was significantly larger than that in Example 1, demonstrating the effectiveness of the inhibitor in suppressing line width growth.
[0121] Comparative Example 2
[0122] 0.5g of zinc acrylate was dissolved in 10g of propylene glycol methyl ether acetate, and 1.25mg of two-photon initiator DETC and 1.25mg of TEMPO were added. The mixture was then sonicated for 20 minutes to promote dissolution. The solution was filtered twice through a 0.22μm filter membrane to obtain the control zinc-based photoresist A. The solution was mixed on a mixer for 24 hours and then stored at 4°C.
[0123] The zinc-based photoresist A was dropped onto a glass substrate and spin-coated at 3000 rpm for 60 seconds to obtain a thin film of the zinc-based photoresist A.
[0124] The etching process was performed using a 780nm femtosecond laser. The laser focus was adjusted using a galvanometer system to induce polymerization of monomers at selected locations in the zinc-based photoresist film. The etching energy was 50mW and the etching speed was 20000μm / s.
[0125] After the inscription is completed, it is developed in propylene glycol methyl ether acetate for 30 seconds, and then developed in isopropanol for 2 minutes to obtain the inscribed pattern.
[0126] The obtained pattern was pyrolyzed in air for 60 minutes using a box furnace at a temperature of 500℃. The heating rate during pyrolysis was 5℃ / min, and the cooling rate was natural cooling.
[0127] Micro- and nano-patterns of zinc oxide can be obtained after pyrolysis, and characterized using SEM, such as... Figure 13 The linewidth of the etched lines is approximately 80 nm. In this comparative example, the monomer was replaced with a zinc-based photoresist monomer. Due to the low sensitivity of zinc-based photoresist, the maximum etch speed at 50 mW energy is only about 20,000 μm / s. Higher speeds would not be able to etch lines. Under these conditions, all other conditions were the same as in Example 1, but the linewidth was much larger than that in Example 1, demonstrating the high sensitivity and high precision characteristics of the copper-based photoresist monomer.
[0128] As can be seen from the images of the copper oxide patterns etched in Examples 1 to 10, the lines etched by this method are clear, with good line shape and uniformity, and a minimum resolution of sub-50 nm. This method can obtain arbitrary copper oxide micro- and nano-patterns through laser direct writing, providing a new approach for the fabrication of copper oxide semiconductor devices.
[0129] The above embodiments provide a detailed description of the present invention, but are not intended to limit the specific implementation of the invention. The present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications based on these embodiments. All obvious modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. A laser-written copper-based photoresist, characterized in that: The laser-written copper-based photoresist comprises a copper-based photoresist monomer, a two-photon initiator, an inhibitor, and a solvent; the inhibitor is at least one selected from 2,2,6,6-tetramethylpiperidine-nitro-oxide, bis(2,2,6,6-tetramethyl-4-piperidinyl-1-oxy) sebacate, and 5,5-dimethyl-1-pyrroline-N-oxide, which inhibits linewidth growth by capturing free radicals diffused during polymerization; in the laser-written copper-based photoresist, the mass of the copper-based photoresist monomer is 2-8% of the mass of the solvent, the mass of the two-photon initiator is 0.25%-2.5% of the mass of the copper-based photoresist monomer, and the mass of the inhibitor is 0.25%-2.5% of the mass of the copper-based photoresist monomer; the copper-based photoresist monomer is hydrated copper methacrylate, copper acrylate, or a mixture of both.
2. The laser-written copper-based photoresist as described in claim 1, characterized in that: The solvent is propylene glycol methyl ether acetate, propylene glycol methyl ether, or a mixture of both.
3. The laser-written copper-based photoresist as described in claim 1, characterized in that: The two-photon initiator is 7-diethylamino-3-thiophenecarboxycoumarin.
4. The laser-written copper-based photoresist as described in claim 1, characterized in that: The laser direct-write copper-based photoresist is composed of copper-based photoresist monomers, two-photon initiators, inhibitors, and solvents.
5. A semiconductor patterning method based on the laser-written copper-based photoresist of claim 1, characterized in that: The semiconductor patterning method includes the following steps: S1: Obtain laser-written copper-based photoresist; S2: Using a spin coater, laser-written copper-based photoresist is spin-coated onto the substrate to form a transparent copper-based photoresist film; S3: A femtosecond laser direct writing device is used, with a femtosecond laser as the light source. The writing method is carried out by a galvanometer. The speed range used during the writing process is 1000 μm / s-200000 μm / s. The copper-based photoresist film is induced to polymerize at the designed position. The design pattern is obtained by developing the film with primary and secondary developer solutions. S4: The pattern etched by the obtained copper-based photoresist is pyrolyzed in an air atmosphere using a heating device. During the pyrolysis process, the organic components in the pattern are oxidized and leave the system, while the copper element is oxidized to copper oxide, resulting in a micro-nano pattern of P-type semiconductor copper oxide.
6. The semiconductor patterning method as described in claim 5, characterized in that: In step S2, the spin coating speed used is 1500-5000 rpm, and the spin coating time is 60 s.
7. The semiconductor patterning method as described in claim 5, characterized in that: In step S3, the wavelength of the femtosecond laser is between 525 and 780 nm. During the etching process, the energy range used for etching the copper-based photoresist is 3-50 mW. The primary developer used for development is at least one of propylene glycol methyl ether acetate, propylene glycol monomethyl ether, and propylene glycol monoethyl ether, and the secondary developer is isopropanol.
8. The semiconductor patterning method as described in claim 5, characterized in that: In step S4, the atmosphere during pyrolysis is air, the pyrolysis temperature is 500-1000 ℃, the heating rate is 1-10 ℃ / min, and the cooling rate is natural cooling.
9. The semiconductor patterning method as described in claim 8, characterized in that: If the pyrolysis temperature of step S4 is 500-600℃, then the substrate used is glass; if the pyrolysis temperature of step S4 is higher than 600℃ but ≤1000℃, then the substrate used is quartz.
Citation Information
Patent Citations
High-precision femtosecond laser direct-writing photoresist composition based on dual-inhibition effect and application of high-precision femtosecond laser direct-writing photoresist composition
CN115793395A
Resin composition, film, wavelength conversion member and method for forming film
TW201710399A